A new species of Lygodactylus (Squamata: Gekkonidae) endemic to Mount Namuli, an isolated ‘sky island’ of northern Mozambique - Portik, Daniel M.; Travers, Scott L.; Bauer, Aaron M.; Branch, William R. (Zootaxa, 2013)
A new species of high elevation dwarf gecko (Gekkonidae: Lygodactylus) is described from Mount Namuli, northern Mozambique. This new species is distinguished from other closely related species in the genus Lygodactylus by body size, scalation, and color, and is genetically divergent from congeners. The species is most similar genetically and morphologically to Lygodactylus rex, the King Dwarf Gecko, which is endemic to Mount Mulanje, Malawi. Mount Mulanje and Mount Namuli are two of several understudied inselbergs forming the southern limit of the Afromontane archipelago in Malawi and Mozambique. The sister taxon relationship of the dwarf gecko species on Mount Mulanje and Mount Namuli illustrates the historical biogeographic connections between these inselbergs, a pattern which is emerging with continued work in this region. The discovery of this new species adds to a growing list of species unique to Mount Namuli, and further establishes this montane region as a conservation priority.